Tanggung Jawab Direksi Perseroan Terbatas yang Dinyatakan Pailit - Machsun Tabroni (Fakultas Hukum Universitas Islam Indonesia, 2002)
This article is intended to discuss about the responsibility's director of limited company that is bankcrutized. In the paragraph 90 the Acts number 1,1995 about Company Limited manage that the director canbe asked for his responsibility personally when the company limited Is stated to be bankrupt. But the director of company limitedmust responsible not by the lawpersonally if the element of mistake Is as the base of responsibility for director as described at paragraph 85 article (1) and (2) the Actsnumber1, 1995 aboutunfulfilled Company Limited.